Innovating digital POE platforms during the COVID-19 pandemic: A case study of co-production in Brazilian social housing - Villa, Simone Barbosa; Stevenson, Fionn; Garrefa, Fernando; de Bortoli, Karen Carrer Ruman; Lya de Melo Carvalho, Nathalia (Frontiers in Built Environment, 2023)
Recognized as a set of methods and instruments applied in environments during use, Post-Occupancy Evaluation (POE) can help manage the project process, providing diagnoses and recommendations that feed new projects and interventions in environments in use. POE approaches have been continually restructured in the face of the new environmental, social, economic and especially technological demands. Especially in the last 5 years, the improvement of POE methodologies and digital interfaces is significant, being facilitated by the dissemination of smart phones connected to the internet, expanding the discussion on new methodological possibilities in the area. In early 2020, the Covid-19 pandemic, lockdowns and quarantines made it challenging to continue to apply traditional face-to-face POE-based tools and techniques. Simultaneously, the MORA Housing Research Group was carrying out a research project in Uberlândia city (Brazil) focusing on the understanding of the relationship between the incidence of arboviruses in the case study social housing neighbourhood, the occupants’ practices, and the built environment management, through POE. The social distancing measures applied during the Covid-19 pandemic led the research team to transform methods from face-to-face to hybrid ones, comprising digital and physical approaches to co-produce durable solutions against dengue. The paper deals with digital POE methods focusing on their reached potential in facilitating the face-to-face experiments demanded by the project. The work comprises a 5 stage method using on-shelf digital platforms and designing other 2 specifically for the project´s purposes. The findings from this project indicate that the incorporation of new digital tools to facilitate physical POE research as a novel hybrid approach provides a successful alternative approach to standard POE processes that are based on face-to-face participation.